Charcot neuroarthropathy after simultaneous pancreas–kidney transplantation: risk factors, prevalence, and outcome. (14th July 2015) - García Barrado, Fernando; Kuypers, Dirk R.; Matricali, Giovanni A.
Abstract: We retrospectively analyzed outcome and risk factors of developing Charcot foot (CF) in 100 patients with type 1 diabetes mellitus who underwent a simultaneous pancreas–kidney (SPK) transplantation. Patients who developed CF after SPK transplantation had significantly higher mortality (56% vs. 18%) and more frequently graft failure (44% vs. 13%). Recipients with CF also experienced acute rejections more frequently (78% vs. 41%). They furthermore had higher pre‐transplant values of HbA1c, received cyclosporine and azathioprine more often, and had significantly higher cumulative corticosteroid use. Patients transplanted in an earlier era (1992–1998) received cyclosporine and azathioprine more often and had a significantly higher cumulative corticosteroid use with the higher prevalence of CF. Conversely, patients with diabetes transplanted more recently (1999–2012) received lower doses of corticosteroids as part of their tacrolimus‐based immunosuppressive therapy, resulting in fewer CF attacks. In conclusion, development of CF after SPK is associated with poor patient and graft outcome. Poor pre‐transplant diabetic control and the use of high‐dose corticosteroids are risk factors for the development of CF. We recommend reduction in or even total avoidance of corticosteroids after SPK transplantation. Given the importance of the diagnosis of CF on outcome, a systematic examination of SPK patients' feet is recommended.